MITOLOGI JEPANG DALAM KOMIK NARUTO KARYA MASASHI KISHIMOTO - Arik Yudiawati, Ni Luh Putu Natalia (Humanis; Volume 5. No. 1. Oktober 2013, 2013)
Mythology concepts are often included into literature work, like novels, comics, etc. Naruto comic is one of the Japanese literature work which is inspired by Japanese mythology. By using the theory of literary anthropology, the Naruto comic is analyzed from the point of view of ethnography to see the cultural aspects of Japanese society. According to the result of the analysis, we can say that Naruto comic is adapting Shinto Gods and Goddess and also youkai from the Japanese mythology. It’s using the name of Shinto Gods as the name of ninja techniques. Those gods are Izanagi no Mikoto, Izanami no Mikoto, Amaterasu Oomikami, Tsukuyomi no Mikoto, and Susanoo no Mikoto. Naruto comic is also told about a supernatural powerful creature called the bijuu. There are three bijuu among nine bijuu which have similarities with the youkai in Japanese mythology. Those youkai are tanuki, nekomata, and kitsune. Although shown in a different form, but the depiction is not separated from the myth.
Keywords: Japanese Mythology, Shinto Gods , Youkai